Different ways to perform actions in different number systems and switch from one number system to another number system - M.M.Otoboyev (Zien Journals, 2022)
in this article, scientific research has been carried out in the fields of implementation of actions in various number systems and various methods of transition from one number system to another number system, as well as the result of reforms carried out in our country today
Keywords: binary number system; divisor; decimal number